2016
DOI: 10.1007/s00464-016-4940-8
|View full text |Cite
|
Sign up to set email alerts
|

One-port video-assisted thoracic surgery versus three-port video-assisted thoracic surgery for primary spontaneous pneumothorax: a meta-analysis

Abstract: Current evidence suggests that one-port VATS may have certain advantages over three-port VATS for PSP. More large-scale and high-quality studies are needed for authentication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
1
21
1
Order By: Relevance
“…The Single port VATS is expected to reduce postoperative pain compared with the conventional VATS because it involves only one intercostal nerve damage; however, clinical benefit remains unclear. When there is no large randomized and prospective study, there are meta-analyzes about postoperative pain after single port and multiport VATS in the primary SP (16)(17)(18). Among those, two meta-analyzes concluded that the single port VATS have shown reduction of pain compared with three-port VATS (16,17), while the other showed that single port VATS had minimal effect of postoperative pain due to heterogeneity, including various surgical techniques and skin incisions (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Single port VATS is expected to reduce postoperative pain compared with the conventional VATS because it involves only one intercostal nerve damage; however, clinical benefit remains unclear. When there is no large randomized and prospective study, there are meta-analyzes about postoperative pain after single port and multiport VATS in the primary SP (16)(17)(18). Among those, two meta-analyzes concluded that the single port VATS have shown reduction of pain compared with three-port VATS (16,17), while the other showed that single port VATS had minimal effect of postoperative pain due to heterogeneity, including various surgical techniques and skin incisions (18).…”
Section: Discussionmentioning
confidence: 99%
“…When there is no large randomized and prospective study, there are meta-analyzes about postoperative pain after single port and multiport VATS in the primary SP (16)(17)(18). Among those, two meta-analyzes concluded that the single port VATS have shown reduction of pain compared with three-port VATS (16,17), while the other showed that single port VATS had minimal effect of postoperative pain due to heterogeneity, including various surgical techniques and skin incisions (18). Most literatures had 1.5-3 cm skin incisions of single port VATS for minor thoracic surgery (16), and we believe that, the ambiguity of terminology defining the single port (uniportal) VATS caused ununiformed conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure aims to inspect the entire pleural cavity, detect the lesion in the parenchyma, [2] resolve the lesion, achieve a chemical pleurodesis with fibrogenetic effect and suppression of pleural space [30] and effective drainage of the pleural cavity [31].…”
Section: Video Assisted Thoracoscopic Surgery (Vats)mentioning
confidence: 99%
“…Conventional three-port VATS has advantage in hospital stay, postoperative pain, and chest drainage time. In 2005, Dr. Gaetano Rocco used simple-port VATS for the first time, a technique that requires a minimum incision of approximately 3 cm and facilitates the postoperative recovery of the patient, compared with three-port VATS [53].…”
Section: Video-assisted Thoracoscopic Surgery (Vats)mentioning
confidence: 99%